Estrategias para el alcance de la participación ciudadana: en la formulación de políticas públicas culturales desde la Secretaría de Cultura del Distrito Metropolitano de Quito - Cuadrado Samaniego, Víctor Hugo (2015)
The study of public policy from his understanding, come to constitute all that the State decide doesn’t do, where institutional contribution is reflected from a research oriented policies and strategies including processes and interventions that seek in the public area, altering the distribution and the production of resources for the production of collective goods and services. The purpose of the investigation is focused on providing building strategies through the formulation of public and cultural policies and specifics details of plans and district projects. Those strengthen and integrate public participation from the Ministry of Culture of the Metropolitan District of Quito. The Public cultural policies since their inception, come to constitute in construction processes, where the District Plan of Cultures provides an analysis of the heterogeneity of actors and approach participatory systems, also we have to mention that the main objective of this investigation is focused in determinate the types of strategies that allow the development of participation in the formulation of public cultural policies from the Ministry of Culture of the Metropolitan District of Quito. This investigation has a quantitative qualitative approach, in the first analyze a socio- cultural reality with the help of theoretical framework that allow identifies the profound nature of the realities one that gives every reason for his behavior and statements. In the qualitative we use collection and analysis of data, allowing answering the question of the investigation and tasting the hypotheses previously established. The results obtained in the analysis of surveys, interviews and citizen participation from the formulation of public cultural policies, have a positive incidence, but with socialization improvements including public officials, cultural managers and citizens of the Metropolitan District of Quito incidence.